Seroepidemiology of pertussis in the east of China: Estimates of incidence of infection in adolescents and adults pre- and post-COVID-19 - Chen, Qiang; Wang, Wen; Shi, Xiuyun; Xu, Yan; Zhu, Yanhong; Wu, Yun; Wang, Zhiguo; Sun, Hui; Sun, Xiang (Frontiers in Public Health, 2022)
Background The dramatic decrease in the number of reported cases of pertussis during COVID-19 pandemic has been underestimated. The objective was to compare the estimated incidence rate of pertussis in populations pre and post-COVID-19 pandemic by analyzing the anti-pertussis toxin (anti-PT) IgG and anti-filamentous hemagglutininant (anti-FHA) IgG antibodies in healthy Chinese population from 2018 to 2021. Methods All serum samples (N=1000) were collected from healthy population (aged ≥15 years) who attended an annual monitoring project of antibody levels in Jiangsu province in 2018-2021 were measured by ELISA. Results The positive rates of anti-PT IgG and anti-FHA IgG antibodies were 11.4% (114/1000) and 20.2% (202/1000) (≥40 IU/ml), the GMC were 17.25(95%CI: 15.49-19.03) IU/mL and 24.94(95%CI: 22.73-27.16) IU/mL in the study population, respectively. The percentage of participants with anti-PT IgG antibodies higher than 40 IU/mL was 5.20% (11/212) in 2018,5.5% (19/348) in 2019, 21.2% (46/217) in 2020 and 17.0%(38/223) in 2021, respectively. The non-detectable rate(<5 IU/mL) of anti-PT IgG antibodies was 16.9%, 17.7%, 28.1% and 37.3% in 2018, 2019 2020 and 2021 respectively. We assumed that the infection occurred within 58.6 days, and based on the overall proportion (2.9%) of individuals with anti-PT IgG antibody ≥100IU/ml, the incidence rate (/100) was estimated by the formula to be 18.08 (95%CI: 12.40-26.11). In addition, the estimated incidence of Post-COVID-19 was higher than that of Pre-COVID-19(36.33/100 vs 12.84/100), and the difference was statistically significant (p<0.05). Conclusions Our results suggest a high rate of under-reporting of pertussis in Jiangsu Province both pre- and post- COVID-19 pandemic, and there are a large number of adults of childbearing age who are susceptible to pertussis.It seems imperative that vaccination of adolescents and adults should be considered for inclusion in vaccination programs.